De la ville usine à la ville globale. Quand les chefs d’entreprise deviennent investisseurs (Monterrey, Mexique) - Leïly Hassaine-Bau (Cahiers des Amériques Latines, 2020)
In San Pedro Garza Garcia, one of the richest Mexican municipalities, market players are mobilizing new tools and new sources of capital in district-level projects. In the hands of a large family, these spaces are urbanized or renovated in the form of new urban objects: a private multifunctional urban complex.This article reveals the strategies of the local elites, from the decision to intervene in a sector with high real estate value, through the mobilization of financial tools, and the conduct of negotiations with local political actors. This work testifies the transition from industrial capitalism to financial capitalism, with changes in urban governance providing answers to the needs of local traditional elites echoing the demands of global financial elites.